2000
DOI: 10.1091/mbc.11.6.1933
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Transport, Assembly, and Degradation of Wild-Type and Disease-linked Mutant Gap Junction Proteins

Abstract: More than 130 different mutations in the gap junction integral plasma membrane protein connexin32 (Cx32) have been linked to the human peripheral neuropathy X-linked Charcot–Marie–Tooth disease (CMTX). How these various mutants are processed by the cell and the mechanism(s) by which they cause CMTX are unknown. To address these issues, we have studied the intracellular transport, assembly, and degradation of three CMTX-linked Cx32 mutants stably expressed in PC12 cells. Each mutant had a distinct fate: E208K C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
126
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 78 publications
7
126
1
Order By: Relevance
“…Consistent with this view, we found that Golgi transit of HERG ⌬860 -899 could not be restored by incubating the cells at room temperature for 12 h (not shown). Similar insensitivity to glycerol and temperature have been described for other HERG mutants (36) as well as for distinct membrane proteins and ion channels that exhibit defective trafficking (37,38). Although the basis of transport block of this class of mutant proteins is unknown, it is possible that these mutations cause a major collapse in protein struc-2 A. Akhavan, R. Atanasiu, and A. Shrier, unpublished data.…”
Section: Discussionmentioning
confidence: 52%
“…Consistent with this view, we found that Golgi transit of HERG ⌬860 -899 could not be restored by incubating the cells at room temperature for 12 h (not shown). Similar insensitivity to glycerol and temperature have been described for other HERG mutants (36) as well as for distinct membrane proteins and ion channels that exhibit defective trafficking (37,38). Although the basis of transport block of this class of mutant proteins is unknown, it is possible that these mutations cause a major collapse in protein struc-2 A. Akhavan, R. Atanasiu, and A. Shrier, unpublished data.…”
Section: Discussionmentioning
confidence: 52%
“…GFPtagged connexins have been widely reported to be functional with essentially unaltered transport and assembly properties (5, 39 -41). Subpopulations of wild-type and Cx43 mutants localized to lysosomes and the Golgi apparatus were not unexpected given the role of lysosomes in Cx43 degradation (32,42,43) and the relatively short half-life (1.5-3.5 h) of Cx43 (44 -46) requiring continual gap junction formation and turnover. Because patients suffering from ODDD would not be expected to express the mutant in the absence of wild-type Cx43, the sole expression of G21R or G138R in N2A or HeLa cells provides valuable insight into the functional state of the mutant but does not accurately mimic the human disease where the mutant and wild-type forms of the protein are likely expressed in equal amounts.…”
Section: Discussionmentioning
confidence: 91%
“…In some cases, these could be considered gain-of-function mutations. The third class of mutants could involve altered intracellular transport and assembly as with some Cx32 mutants associated with Charcot-Marie-Tooth disease (32) or Cx26 mutations linked to deafness and skin disease (33)(34)(35). This class of mutants may in fact be functional if transported to the cell surface in association with wild-type proteins, not unlike mutations of the chloride channel responsible for cystic fibrosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…In both mammalian cells and in yeast, it has been shown that a post-endoplasmic reticulum quality control mechanism appears to be responsible for targeting and lysosomal/vacuolar degradation of misfolded membrane proteins (42)(43)(44)(45). The presence of a cytosolic portion may be a prerequisite for the detection of partly unfolded Mpl by the post-endoplasmic reticulum quality surveillance system.…”
Section: Discussionmentioning
confidence: 99%